Pengaruh Perkembangan Usaha Mikro, Kecil dan Menengah Terhadap Pendapatan Nasional di Indonesia Pada Tahun 2010-2013 - Amelia Pratiwi; Dina Januarti; Dwi Sunarti; Dini Hidayati Nafiah; Mustofa . (Peneliti.net, 2023)
The significant impact on the national income highlights the value of expansion and economic development in Indonesia. Micro, small, and medium enterprises (UMKM) play a crucial role in the overall tax revenue of the country. By utilizing secondary data collected by the Central Statistics Agency (BPS), this research attempts to measure the influence of UMKM growth on Indonesia's GDP between 2010 and 2013. Descriptive qualitative analysis is the method employed in compiling this research data. The findings of this study demonstrate that the sector that can provide a fairly relevant contribution to the country's GDP through labor and investment is the UMKM sector. Micro, small, and medium enterprises (UMKM) have an important role in driving the development of new markets and creating new job opportunities. Their contribution can enhance Indonesia's GDP and overall balance of payments, thereby increasing their significance in fostering opportunities and economic growth.